Peran Zakat Dan Wakaf Dalam Menjaga Stabilitas Ekonomi Makro Islam - Sukma, Ebi; Rahayu, Karmilawati Dwi; Risdayani, Nabilla; Sagita, Nadra; Hendra, Joni (Yayasan Rahmat Islamiyah, 2024)
Zakat and waqf are two Islamic financial instruments that have great potential in maintaining macroeconomic stability. This study aims to analyze the role of zakat and waqf in maintaining Islamic macroeconomic stability. This topic was chosen because of the gap between the potential of zakat and waqf with the realization of its collection and utilization which is still low. In addition, macroeconomic instability is common in Muslim countries. The research methods used are literature studies and secondary data analysis related to zakat, waqf, and macroeconomic indicators. Data were collected from reports from zakat and waqf institutions, as well as national and international statistical agencies. The analysis was conducted by looking at the correlation between the collection and distribution of zakat and waqf with macroeconomic indicators such as economic growth, inflation, unemployment, and poverty. The results showed that zakat and waqf have a significant role in maintaining Islamic macroeconomic stability. Optimal collection and distribution of zakat can reduce poverty and income inequality, and encourage consumption and investment In conclusion, zakat and waqf have proven to be able to maintain Islamic macroeconomic stability by reducing inequality, encouraging consumption and investment, and providing adequate infrastructure and public services.